2023
DOI: 10.2196/41091
|View full text |Cite
|
Sign up to set email alerts
|

Research Status and Emerging Trends in Virtual Reality Rehabilitation: Bibliometric and Knowledge Graph Study

Abstract: Background Virtual reality (VR) technology has been widely used in rehabilitation training because of its immersive, interactive, and imaginative features. A comprehensive bibliometric review is required to help researchers focus on future directions based on the new definitions of VR technologies in rehabilitation, which reveal new situations and requirements. Objective Herein, we aimed to summarize effective research methods for and potential innovativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Fan. T [23] , found that VR gaming significantly enhanced motor recovery and promoted stroke patients' treatment plans. VR based games gaining popularity but still need to be explored for effective stroke rehabilitation.…”
Section: Effectiveness Of Immersive Virtual Reality Based Hand Rehabi...mentioning
confidence: 99%
“…Fan. T [23] , found that VR gaming significantly enhanced motor recovery and promoted stroke patients' treatment plans. VR based games gaining popularity but still need to be explored for effective stroke rehabilitation.…”
Section: Effectiveness Of Immersive Virtual Reality Based Hand Rehabi...mentioning
confidence: 99%
“…23 Combining LLM and KGs to ensure LLM output factualness: A knowledge graph represents a network of real‐world entities—that is, objects, events, situations, or concepts—and illustrates the relationships between them. Clinical researchers have built various LBP‐related knowledge graphs, for example, encoding the LBP concepts and knowledge and their interrelations with a focus on Virtual Reality rehabilitation 24 and central sensitization. 25 Unlike LLMs, whose knowledge is implicit and difficult to scrutinize, a KG explicitly visualizes the concepts and knowledge it learns from medical texts.…”
Section: The Potential Of Knowledge Organizing Technologies For Trans...mentioning
confidence: 99%
“…Virtual reality (VR) is emerging as a swiftly advancing technology, garnering recent popularity as a promising support tool for neurorehabilitation among individuals with ABI [10][11][12][13]. Using VR in rehabilitation represents a versatile, captivating, and multifaceted approach capable of addressing patients' sensorimotor and cognitive capacities, thereby eliciting positive responses.…”
Section: Introductionmentioning
confidence: 99%
“…As the term "virtual reality" can encompass various computer-based rehabilitation system types across studies and may influence the feasibility and efficacy of interventions, maintaining consistent terminology is crucial [12,16]. In 1999, Brooks [17] defined a VR experience as "any in which the user is effectively immersed in a responsive virtual world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation